2016
DOI: 10.4191/kcers.2016.53.4.411
|View full text |Cite
|
Sign up to set email alerts
|

Solvent Vapor Annealing Effects in Contact Resistances of Zone-cast Benzothienobenzothiophene (C8-BTBT) Transistors

Abstract: Benzothienobenzothiophene (C 8 -BTBT) is a soluble organic small molecule material with high crystallinity resulting from its strong self-organizing properties. In addition, the high mobility and easy fabrication of C 8 -BTBT make it very attractive in terms of organic thin-film transistors. In this work, we made C 8 -BTBT thin films by using the zone-casting method; we also used an organic solvent to treat the devices with solvent vapor annealing to improve the electrical properties. As a result, we confirmed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Due to the low thermal expansion, 1) low Young's modulus and high melting point of 2 133 K, they had been used as an insulation material in engine components such as piston bottom, port-liners, and turbochargers etc. 2) There has been some investigations on the synthesis and properties of Al 2 TiO 5 . Hans Wohlfromm 3) studied the formation of Al 2 TiO 5 by sintering the Al 2 O 3 /TiO 2 multilayers in the temperature range from 1 473 to 1 773 K, and it was found that TiO 2 played an important role in the initial growth of Al 2 TiO 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Due to the low thermal expansion, 1) low Young's modulus and high melting point of 2 133 K, they had been used as an insulation material in engine components such as piston bottom, port-liners, and turbochargers etc. 2) There has been some investigations on the synthesis and properties of Al 2 TiO 5 . Hans Wohlfromm 3) studied the formation of Al 2 TiO 5 by sintering the Al 2 O 3 /TiO 2 multilayers in the temperature range from 1 473 to 1 773 K, and it was found that TiO 2 played an important role in the initial growth of Al 2 TiO 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Generally, the size and quality of organic crystals can be tailored by the physical and chemical properties of the mixed solution, surface properties of the substrates (temperature and surface energy), and deposition parameters of the bar-coating. 21 The pristine TIPS-pentacene or blended TIPS-pentacene/PS solution was dispersed on the bar-coating substrates. The bar-coating parameters can control the evaporation of the solution and, subsequently, manage the level of nucleation and crystal growth of the TIPS-pentacene films.…”
Section: Methodsmentioning
confidence: 99%
“…1 wt% SiO 2 and 1 wt% Y 2 O 3 were added for consistency. In addition, the sol‐gel technique can be used to prepare Al 2 TiO 5 particles . This technique includes production of solution with titanium tetrabutoxide, aluminum chloride, and monohydrate citric acid and ethanol at relatively lower temperatures.…”
Section: Introductionmentioning
confidence: 99%